Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/path.4325
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the genomic features and expressed fusion genes in micropapillary carcinomas of the breast

Abstract: Micropapillary carcinoma (MPC) is a rare histological special type of breast cancer, characterized by an aggressive clinical behaviour and a pattern of copy number aberrations (CNAs) distinct from that of grade- and oestrogen receptor (ER)-matched invasive carcinomas of no special type (IC-NSTs). The aims of this study were to determine whether MPCs are underpinned by a recurrent fusion gene(s) or mutations in 273 genes recurrently mutated in breast cancer. Sixteen MPCs were subjected to microarray-based compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
122
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 92 publications
(129 citation statements)
references
References 58 publications
(99 reference statements)
7
122
0
Order By: Relevance
“…In contrast, extracranial MRD was predicted by ctDNA mutation tracking in all patients who relapsed (n = 12) (P = 0.0022, c 2 test with Yates' correction). Once mutation tracking had confirmed the presence of MRD, we sequenced DNA from the primary cancer, from the residual primary tumor resected after chemotherapy, from the plasma DNA taken before relapse, and from the subsequent metastasis when biopsied, in five patients with a panel targeting all exons of 273 genes recurrently mutated in breast cancer (17). The sequencing strategy was optimized for low DNA inputs using hybrid capture with a custom NimbleGen SeqCap EZ Choice library followed by sequencing on a HiSeq2000 to a mean target depth after duplicate removal of 460× (range, 104× to 1015×).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, extracranial MRD was predicted by ctDNA mutation tracking in all patients who relapsed (n = 12) (P = 0.0022, c 2 test with Yates' correction). Once mutation tracking had confirmed the presence of MRD, we sequenced DNA from the primary cancer, from the residual primary tumor resected after chemotherapy, from the plasma DNA taken before relapse, and from the subsequent metastasis when biopsied, in five patients with a panel targeting all exons of 273 genes recurrently mutated in breast cancer (17). The sequencing strategy was optimized for low DNA inputs using hybrid capture with a custom NimbleGen SeqCap EZ Choice library followed by sequencing on a HiSeq2000 to a mean target depth after duplicate removal of 460× (range, 104× to 1015×).…”
Section: Resultsmentioning
confidence: 99%
“…IMPC more often harboured gains of chromosomes 1q, 8q, 17q and 20q, and losses of 1p, 8p, 13q, 16q and 22q,13 14 which were emphasised by Marchio and coauthors13 as previously associated with breast tumours of high histological grade. In contrast, concurrent gain of 1q and 16p and deletion of 16q, related to low tumour grade according to the literature data, were less found in IMPC 13.…”
Section: Introductionmentioning
confidence: 84%
“…33,58 Many genes related to maintaining polarity, cilia formation, and cell morphology are located in these regions. Hao et al 59 compared the expression of prostate stem cell antigen (PSCA) gene located at 8q24 in 66 cases of IMPCs and 67 cases of ICD-NOSs and found that its expression was significantly greater at both the protein and messenger RNA levels in IMPC than it was in IDC-NOS.…”
Section: Mechanism Of Metastasismentioning
confidence: 99%